2013
DOI: 10.1002/smll.201302136
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Theranostic Nanoparticles: Receptor‐Mediated Entry into Cells, pH‐Induced Signal Generation and Cytosolic Delivery

Abstract: Virus-like theranostic nanoparticles: virus-like poly(amino acid) nanoparticles are synthesized that can be internalized via receptor-mediated endocytosis, resulting in encapsulated pH-activatable fluorescence probes that can be turned on in acidic environments but otherwise remain undetectable. The encapsulated anticancer drugs are also released into cytosol by endosome disruption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…In a similar manner, Lee et al employed a BODIPY group that is activated under slightly acid condition to construct biosynthetic polypeptide‐based nanoparticles. The nanoparticles possess the ability to display pH‐induced turn‐on fluorescence, delivery of anticancer drugs and enhancement of receptor‐mediated endocytosis . In 2015, Tian et al also developed a diethylaminophenyl substituted BODIPY‐based pH‐activatable theranostic nanosystem .…”
Section: Examples Of Cancer‐associated Stimuli‐driven Turn On Theranomentioning
confidence: 99%
“…In a similar manner, Lee et al employed a BODIPY group that is activated under slightly acid condition to construct biosynthetic polypeptide‐based nanoparticles. The nanoparticles possess the ability to display pH‐induced turn‐on fluorescence, delivery of anticancer drugs and enhancement of receptor‐mediated endocytosis . In 2015, Tian et al also developed a diethylaminophenyl substituted BODIPY‐based pH‐activatable theranostic nanosystem .…”
Section: Examples Of Cancer‐associated Stimuli‐driven Turn On Theranomentioning
confidence: 99%
“…Nanoparticles (NPs), carbon nanosheets or nanotubes, and DNA‐based nanostructures hold great promise for quantitative detection of protein, DNA, and small molecules . Alternatively, they can also serve as vehicles to deliver biological molecules into cells and animals . More recent in vitro studies showed that several types of nanomaterials own intrinsic enzyme‐like activities (e.g., peroxidase, glucose oxidase), which have proven useful in biosensing or biomedical diagnosis .…”
mentioning
confidence: 99%
“…b) Target-selective theranosis: receptor-mediated entry of γ-PGA- g -cetylester [pSF/paclitaxel] nanoparticles followed by pH-dependent signal-on, hydrophobicity-induced membrane-disruption and cytosolic delivery of therapeutic drugs. Reprinted with permission from Reference 317. Copyright 2014 John Wiley & Sons, Inc.…”
Section: Figurementioning
confidence: 99%